CFD modeling of reactive species air cleaner applications in a classroom - Youngbo Won; William Bahnfleth; John Cimbala (Indoor Environments)
Due to increasing concerns related to airborne virus spread indoors, more reactive species air cleaners are being utilized in classrooms. Reactive species generated by air cleaners decompose airborne pathogens chemically, decreasing the risk of infection. Due to the high reactivity of these oxidants, reactive species may be distributed nonuniformly in indoor environments, as are viral aerosols emitted by infectors. Heterogeneous distributions of reactive species may cause spatially non-uniform removal rates of viral aerosols. However, there is little information regarding spatial distributions of either reactive species or viral aerosols in ventilated classrooms. Thus, the objective of this study was to investigate spatial distributions of reactive species and infectious aerosols and to examine how operating conditions of air cleaners affect viral aerosol removal rates. A CFD model simulated the operation of a reactive species air cleaner generating hydrogen peroxide (H2O2) in a mechanically ventilated 237 m3 classroom with nine occupants. The reactive species air cleaner showed a 3–20 times higher equivalent air change rate to a HEPA filter air cleaner with the same inlet and outlet flows. During the operation of reactive species air cleaners, elevated viral aerosol concentration was confined to regions near infectors. This was due to the high reactivity of reactive species, decreasing the infection probability of receptors from 3.2 % to 0.1 % with a 1-hour exposure time. As the room average concentration of reactive species increased from 15.6 to 50.4 ppb, both below the US Occupational Safety and Health Administration (OSHA) Permissible Exposure Limit (PEL) of 1000 ppb, the room average infection probability decreased from 0.3 % to 0.1 %. Due to the residence times of reactive species, the location of reactive species air cleaners affected the inactivation rate of viral aerosol, resulting in a 24 % variation of concentration difference of infectious aerosol with air cleaner locations.